2005
DOI: 10.1209/epl/i2004-10525-6
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic dynamics of magnetosomes in cytoskeleton

Abstract: Rotations of microscopic magnetic particles, magnetosomes, embedded into the cytoskeleton and subjected to the influence of an ac magnetic field and thermal noise are considered. Magnetosome dynamics is shown to comply with the conditions of the stochastic resonance under not-too-tight constraints on the character of the particle's fastening. The excursion of regular rotations attains the value of order of radian that facilitates explaining the biological effects of low-frequency weak magnetic fields and geoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…As was derived in Binhi and Chernavskii [2005], the sensitivity of the rate of the well-to-well transitions to slow variations in the dc MF magnitude is equal to 200 nT, in order of magnitude. This gives a way to measure the geomagnetic field strength as a signal proportionate to the rate of transitions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As was derived in Binhi and Chernavskii [2005], the sensitivity of the rate of the well-to-well transitions to slow variations in the dc MF magnitude is equal to 200 nT, in order of magnitude. This gives a way to measure the geomagnetic field strength as a signal proportionate to the rate of transitions.…”
Section: Discussionmentioning
confidence: 86%
“…In this case, the motion of the magnetosomes in an additional ac MF meets the conditions of the so-called ''stochastic resonance'' that facilitates explaining the biological effects of low frequency weak MFs [Binhi and Chernavskii, 2005]. Slow variations in the dc MF magnitude were also shown to control the well-to-well transitions effectively.…”
Section: Modelmentioning
confidence: 80%
“…Binhi also theoretically analyzed the generation of free radicals by MNPs in a static magnetic field (0.4 T) and found that MNPs can increase the rate of free radical formation [110]. Besides, magnetic field generated by MNPs around themselves is orders of magnitude greater than the applied magnetic field [106,111].…”
Section: Effect Of Free Radicalmentioning
confidence: 99%
“…Notice, that a two-stage relaxation of the closed times P (τ ) cannot be described by a simple sequential Markovian scheme with just two closed substates, C 2 ↔ C 1 → O. This is because: (i) the relative weight of two stages depends very essentially on the detection threshold, (ii) initial stage is described by the Pareto power law (24) and not by an exponential.…”
Section: A Markovian Dynamicsmentioning
confidence: 99%